2009
DOI: 10.1146/annurev.pathol.4.110807.092317
|View full text |Cite
|
Sign up to set email alerts
|

Serrated Polyps and Colorectal Cancer: New Pathway to Malignancy

Abstract: Until recently, two major forms of colorectal epithelial polyp were recognized: the adenoma and the hyperplastic polyp. Adenomas were perceived to represent the precursor to colorectal cancer, whereas hyperplastic polyps were viewed as innocuous lesions with no potential for progression to malignancy. We now recognize, however, that the lesions formerly classified as hyperplastic actually represent a heterogeneous group of polyps, some of which have a significant risk for neoplastic transformation. These serra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
183
1
6

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 244 publications
(195 citation statements)
references
References 124 publications
5
183
1
6
Order By: Relevance
“…The morphologic, clinical, and molecular characteristics of sporadic colorectal serrated polyps are well-recognized, [2][3][4][5]8,23 and have resulted in consensus recommendations for short-and long-term patient management. 7,24,25 The present study addresses the dearth of available data regarding such lesions in patients with inflammatory bowel disease by means of a retrospective evaluation of serrated polyps diagnosed during the course of endoscopic surveillance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The morphologic, clinical, and molecular characteristics of sporadic colorectal serrated polyps are well-recognized, [2][3][4][5]8,23 and have resulted in consensus recommendations for short-and long-term patient management. 7,24,25 The present study addresses the dearth of available data regarding such lesions in patients with inflammatory bowel disease by means of a retrospective evaluation of serrated polyps diagnosed during the course of endoscopic surveillance.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Sessile serrated adenoma/polyps are usually located in the proximal colon, predominate in women, and harbor BRAF mutations, whereas traditional serrated adenomas are usually left sided, occur more often in men, and contain KRAS mutations. [3][4][5] The significance of serrated polyps in the general population with respect to carcinoma risk stratification, endoscopic surveillance, and management is becoming increasingly clear and has recently been incorporated into clinical consensus guidelines. [6][7][8] Patients with extensive, longstanding colonic inflammatory bowel disease, mainly ulcerative and Crohn's colitis, face an increased risk of developing colorectal cancer compared with the general population.…”
mentioning
confidence: 99%
“…The key element of this pathway is dysfunction in DNA mismatch repair enzymes that results from germline mutations in one of several DNA mismatch repair genes, most commonly MLH1 or MSH2. The result is the development of microsatellite instability (MSI) in tumors derived through this genetic pathway [33].…”
Section: Mcamentioning
confidence: 99%
“…1 However, the biological significance of these two morphological patterns is still unknown. Although some pathologists diagnose tumors with combined features as mixed hyperplastic/adenomatous polyps or mixed polyps with a description of the constituent components, 17,18 mixed polyps have also been reported to share similar molecular changes and implicate morphological progression to malignancy. 13,19 Jass et al 13 reported that traditional serrated adenoma with dysplastic epithelium resembling conventional adenoma displayed a high frequency of KRAS mutation, whereas Kim et al 7 linked this traditional serrated adenoma to a lower frequency of BRAF mutation.…”
mentioning
confidence: 99%